2021
DOI: 10.5617/osla.8913
|View full text |Cite
|
Sign up to set email alerts
|

French as a third language in Norway: The influence of the prior languages in the acquisition of word order

Abstract: The present study investigated the acquisition of verb movement in L3 French by L1 speakers of Norwegian with English as their L2. To investigate the impact of previously learned languages in L3 acquisition, we looked at two sentence types with lexical verbs where Norwegian, English, and French differ in systematic ways: a) non-subject initial declarative main clauses and b) subject-initial declarative main clauses with a short sentence-medial adverbial. Students completed acceptability judgment tasks in both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…This has been argued, for example, by Listhaug et al. (2021), who found influence from both L1 Norwegian and L2 English in L3 French, as well as by Westergaard et al. (2017), Jensen et al.…”
Section: Background Literaturementioning
confidence: 66%
See 2 more Smart Citations
“…This has been argued, for example, by Listhaug et al. (2021), who found influence from both L1 Norwegian and L2 English in L3 French, as well as by Westergaard et al. (2017), Jensen et al.…”
Section: Background Literaturementioning
confidence: 66%
“…Thus, a possible explanation is that V3 (XSV) represents an unmarked word order in the sense that it involves no syntactic movement. Several other studies (e.g., Listhaug et al., 2021; Stadt et al., 2020) have found a general preference for nonmovement over movement in different L3 populations. Another, and possibly related, explanation is that this asymmetry reflects a foreign language/L2 effect, but only when cues are incongruent because we did not observe the same in congruent inputs where the lexicon alone indicated a similarity to a preexisting grammar (Figure 5).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…We investigate how the (non-)correspondence in surface structure in speakers' previously acquired languages affects the acquisition of verb placement in specific structures in the L3. Previous research has found that learners performed better with non-subject-initial main clauses (where their L2 English had a corresponding structure) than with subject-initial main clauses with adverbs (where their L1 Norwegian displayed corresponding surface structure) (Listhaug et al, 2021). In the current study, we investigate these same structures in addition to relative clauses with adverbs, where neither Norwegian nor English surface structure corresponds to French.…”
mentioning
confidence: 90%
“…In the current study, we investigate the same structures as Listhaug et al (2021), namely non-subject-initial main clauses without sentence-medial adverbs (Non-SU-I) and subject-initial main clauses with a sentence-medial adverb (SU-I-MC) in L3 French learners at university level. Additionally, we further investigate the hypothesis that economy plays a role in transfer 1 by looking at verb placement relative to adverbs in subject-initial relative clauses (SU-I-RC), where neither Norwegian nor English verbs move, but French verbs do, meaning neither Norwegian nor English has similar surface word order to French.…”
Section: Introductionmentioning
confidence: 99%